Pelestarian Seni Jaran Kepang oleh Sanggar Wahyu Satrio Putro di Kota Binjai - Tarigan, Yohana Amerisa Br; Dewi, Heristina; Gulo, Hubari (Mahesa Research Center, 2025)
This study examines the preservation of the Jaran Kepang art form by Sanggar Wahyu Satrio Putro in Binjai City using a qualitative approach. The objectives of the research include: (1) adaptation and innovation without compromising traditional values, and (2) passing down Jaran Kepang to younger generations. Jaran Kepang is a traditional Javanese art that portrays the skills of horseback warriors through dynamic and captivating dance movements, accompanied by gamelan music. Although this art form has existed since the Majapahit Kingdom, its development outside Java, including in Binjai City, North Sumatra, reflects a cultural transformation. The study applies a qualitative method through non-participant observation, interviews, video recordings, and audio documentation. The findings reveal that the preservation of Jaran Kepang by Sanggar Wahyu Satrio Putro is not merely an act of safeguarding cultural heritage, but also a strategic effort to maintain the relevance of traditional arts in the era of globalization.